Effects of different modes of ultrasonic assisted low-temperature curing on beef quality - WU Mengdi; MA Haile; LIU Huimin (Shipin yu jixie, 2023)
Objective: This study aimed to discover a green, fast curing method for the domestic refrigerator freezer. Methods: Under the control of low-temperature condition, different frequency combination of ultrasonic assisted curing beef was used to study its effect on beef quality. Results: Compared with low-temperature static curing, simultaneous ultrasonic 22+40 kHz (SIU 22+40 kHz) had the best curing effect, and the salt content (0.327 4%) was increased by 74.15% (P＜0.05), with the cooking loss (34.933%) reduced by 11.45% (P＜0.05). The hardness (293.545 N) was reduced by 18.39% (P＜0.05), and the resilience (1.436N/mm2) was reduced by 17.54% (P＜0.05), with the chewiness (2 209.964 N/mm) reduced by 20.12% (P＜0.05). Conclusion: Under the low temperature condition of 2~6 ℃, ultrasonic-assisted low temperature salting can effectively increase the salt content, reduce the cooking loss, improve the tenderness, and better maintain the color quality of beef. The curing effect of sequential ultrasonic (SEU) and synchronous ultrasonic (SIU) assisted low temperature curing was better than that of single frequency ultrasonic (MU) assisted low temperature curing. The curing effect of sequential ultrasonic (SEU) and simultaneous ultrasonic (SIU) assisted low-temperature curing was better than that of mono-frequency ultrasonic (MU) assisted low-temperature curing.